2003
DOI: 10.1002/masy.200350915
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of semifluorinated polymers and block copolymers

Abstract: The goal of the investigation presented here was to evaluate the influence of semifluorinated side chains on the bulk structure and the surface properties of polysulfones with different chain structure. Thus, segmented block copolymers consisting of polysulfone and semifluorinated aromatic polyester segments as well as polysulfones having semifluorinated side chains randomly distributed over the polymer backbone were synthesized and characterized. Oxydecylperfluorodecyl side chains were used because of their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…All polymers under discussion were synthesized by transesterification polycondensation in the melt, using for the fully aromatic polymers 1e2 transacetylation polycondensation [6,8] and for the semiaromatic polymers 3e8 transesterification of dimethyl esters with the aliphatic diols [10,17]. The chemical characterization of the polymers used for the current investigation is summarized in Table 2.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…All polymers under discussion were synthesized by transesterification polycondensation in the melt, using for the fully aromatic polymers 1e2 transacetylation polycondensation [6,8] and for the semiaromatic polymers 3e8 transesterification of dimethyl esters with the aliphatic diols [10,17]. The chemical characterization of the polymers used for the current investigation is summarized in Table 2.…”
Section: Synthesismentioning
confidence: 99%
“…If such semifluorinated segments are attached to polymeric backbones, the microphase separation of the semifluorinated segments can often be maintained assuming that the number of C-atoms in the semifluorinated (SF) segments (in both alkyl and perfluoroalkyl parts) is above a critical value. This is demonstrated for a set of polymers with varying polymer backbones and different semifluorinated side chains, for instance semifluorinated polystyrene [3], polystyreneepolyisoprene diblock copolymers [4], polymethylmethacrylate [5], polyesters [6e9], polysulfones [10], segmented polyestere polysulfone block copolymers [11,12] and others. In special cases where the semifluorinated side chains are long enough, the ordered solid-state results in the formation of a wellorganized surface structure, resulting in polymeric materials with extremely low surface free energy [13e16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pospiech et al synthesized aromatic polyesters based on 5‐hydroxy isophthalic acid with semifluorinated side chains and found that poly( p ‐phenylene isophthalate) with oxydecylperfluorodecyl side chains formed a self‐organizing liquid crystalline structure that resulted in low values of surface free energy 34,35…”
Section: Liquid‐crystalline Fluorinated Block Copolymersmentioning
confidence: 99%
“…The internal microphase separation leads mostly to smectic layered structures in which the backbones and layers of SF side chains alternate Pospiech et al, 2003b). Former experiments examined in detail the behaviour of different polymers with H10F10 side chains [-O-(CH 2 ) 10 -(CF 2 ) 10 -F] Pospiech et al, 2003a). Combination of different scattering methods and thermal treatments yielded in understanding the special side chain structure characterized by interdigitation and tilt of side chains (Jehnichen et al, 2004;Jehnichen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%